An exploration of high school learners’ perceived utility of career guidance in a public township high school - Mailula, Kutloano (My University, 2021)
The current study explored high school learners’ perceived usefulness of career guidance in a public township high school. The sample consisted of twelve learners from a Gauteng township high school in Mamelodi. The main aims of the study were to explore township learners’ perceptions of the approach used during career guidance in school and the quality of information received. The role career guidance played in readying learners to make career related decisions was also explored. The study was guided by the Systems Theory Framework of career development and was qualitative in nature. A semi-structured interview guide was used to collect data and the thematic analysis method was used to analyse the data. The main findings highlighted that learners believed career guidance could be an integral aspect of their career choice process. They were, however, not satisfied with the career guidance process they experienced. Inadequate information and teacher involvement were some of the issues highlighted. Learners also reported unsatisfactory experiences with regard to career expos because of a variety of reasons including overcrowded sessions and insufficient time allocations to engage with career advisors. These factors were found to substantially diminish the role career guidance plays in aiding learners to make sensible career choices. The research study suggests that in order for learners to be effectively guided in their career decision making process, teacher involvement and the quality of career choice information and need to improve and be more bespoke. Furthermore, events like career expos should be given careful consideration before schools encourage students to attend.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Social and Psychological Research to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021